Strategic management competitiveness ad globalization concepts and cases - Michael A. Hitt (Australia Cengage, 2020)
Examine strategic management with the market-leading book that sets the standard as today's most intellectually rich, practical analysis of strategic management. Written by prominent management scholars and award-winning instructors, Hitt/Ireland/Hoskisson's STRATEGIC MANAGEMENT: COMPETITIVENESS AND GLOBALIZATION, 13E incorporates cutting-edge research and new examples from more than 600 companies to reveal how firms effectively use the strategic management process. This edition combines a classic industrial organization model with a resource-based view of the firm to demonstrate how businesses establish competitive advantages and create value for stakeholders in the global marketplace. You study how firms govern themselves, the value of strategic alliances to global companies and the value firms create by melding strategic management and entrepreneurial behaviors when competing. MindTap online learning solution is also available with new real-world activities designed to help you outperform and excel as a strategic leader.
Keywords: Strategic management